Two-dimensional layered materials integrated with oxide semiconductor-based hybrid devices for broadband photodetector applications - Kumawat, Kishan Lal; advised by Rajamalli, P; Nanda, K K and Krupanidhi, S B (Bangalore: Indian Institute of Science, 2023)
Photodetectors find their applications in several arenas such as that of bio-integrated electronics, health monitoring, high-definition imaging, remote controls, spectroscopy, and others. Therefore, photodetectors play an indispensable role in our lives and, advancement in these devices could solve further challenges associated with them. Such challenges include the elimination of external power source in the present-day commercially available photodetectors, spectral discrimination, etc. Several attributes of conventional semiconductors-based photodetectors need further rectification and improvement. Some of the drawbacks are low spectral coverage, low resolution, the requirement of optical filters for colour discrimination, and that of high-power consumption for operation. Such limitations warrant the exploration of alternative photodetector material, which may help alleviate the bottleneck that the current situation presents. Of them, graphene, has been found to be one of the most promising and well-studied two-dimensional layered materials. After the discovery of graphene, several other layered materials, such as MoS2, WS2 and others, have received attention. Two-dimensional materials show broad spectral coverage with high mechanical flexibility. They also show excellent optical and electronic properties because of their tuneable band gap which can be altered by changing the number of layers and the thickness of the film. Apart from these properties, they possess high charge carrier mobility and significant light absorption. In addition, they are easy to fabricate and highly transparent for portable and flexible electronics. Also, they exhibit a wide absorption of near infra-red (NIR) and visible wavelengths. Therefore, two-dimensional layered materials are suitable for broadband photodetector applications. Among them, MoS2 has gained special attention due to its n-type semiconductor behaviour, high charge carrier mobility, in addition to its excellent stability. Also, the absence of dangling bonds at the surface of MoS2 overcomes the constraints of lattice mismatch and facilitates its integration with semiconductor oxides such as SnO2, CuO and ZnO with fewer interfacial defects. The integration of MoS2 with metal oxides, is our material of choice, due to their extremely low cost, ease of fabrication and excellent chemical and thermal stability. Additionally, the combination of MoS2 with metal oxide semiconductors yields better charge separation and transportation, which can, in turn, fuel self-powered and broadband photodetector devices. The following presents the findings of the work carried out in this thesis. The results have been organized in 8 chapters; a summary of each chapter is given below: Chapter 1 discusses the applications, types, working mechanism, and figures of merit of photodetector devices. The drawbacks of current photodetector devices, along with the merits of two-dimensional layered materials when employed for photodetection applications, are briefly outlined. The heterostructures of two-dimensional layered materials with metal oxides have also been discussed. Chapter 2 describes the experimental techniques, that were used for material synthesis, device fabrication and electrical characterization. Chapter 3 presents the broadband photodetection studies based on reduced graphene oxide (RGO) photodetector device. RGO device shows broadband photodetection with maximum responsivity in the NIR region. Mid gap states present in the band gap of RGO trap electrons, whereas isolated molecular states facilitate the transport of holes through hopping, which in turn, results in high device performance. Chapter 4 reports the fabrication and photoresponse studies of an MoS2/SnO2-based hybrid photodetector device. The device shows self-powered behaviour with broadband photodetection ranging from UV-visible to NIR wavelengths. The photoresponse of the photodetector device is affected by the defect states and a small junction barrier originates at the MoS2/SnO2 heterointerface. Chapter 5 presents a self-powered broadband photodetector device based on the MoS2/CuO heterojunction. The photodetector device shows thousand-fold improvement in responsivity at applied reverse bias, which is attributed to the high rectifying nature of photocurrent. Here the formation of p-n junction facilitates the charge carrier separation and their transportation to the external electrodes which leads to high photoresponse. Chapter 6 presents the study of the photodetection properties of an MoS2/ZnO device. The device predominantly exhibits UV photoresponse at low bias and NIR photoresponse at high applied bias. Therefore, this photodetector device discriminates the photons of UV wavelengths from that of NIR, when modulated through the applied bias. Chapter 7 reports a highly efficient self-powered, broadband photodetector device based on a SnSe2-RGO/MoS2 hybrid photodetector device. Here, SnSe2 and RGO are blended to form a bulk heterojunction and SnSe2-RGO composite, rather than integration with MoS2. Incorporation of SnSe2 in RGO drastically increases the interface area, which reduces the exciton diffusion path length and facilitates charge carrier separation. Moreover, the SnSe2-RGO/MoS2 heterostructure is energetically favourable for effective charge separation via generation of a built-in potential. Thus, the device exhibits excellent responsivity and high detectivity upon irradiation with IR light, coupled with high reproducibility and stability. Chapter 8 gives an overall summary and conclusion of the work presented in the thesis.
includes bibliographical references and index
PhD; 2023; Materials Research Centre
Keywords: Photodetectors; Sputtering; Two-dimensional layered semiconductors